Shifts in aquatic insect composition in a tropical forest stream after three decades of climatic warming. (18th September 2020) - Dudgeon, David; Ng, Lily C. Y.; Tsang, Toby P. N.
Abstract: The effects of climatic warming on tropical streams have received little attention, and field studies of such changes are generally lacking. Drifting insects from a Hong Kong forest stream were sampled for 36 months between 2013 and 2016, and compared with samples collected using identical methods in 1983–84. Mean air temperatures rose by ~0.5°C (0.17°C per decade) over this period. The stream drained an uninhabited protected area, so no climate‐change effects were confounded by anthropogenic disturbance. In total, 105 taxa and >77, 000 individuals were collected. Richness of samples in the historic and contemporary datasets did not differ, but true diversity of drifting insects was highest in 1983–84, and declined between 2013–14 and 2015–16. There was considerable disparity in assemblage composition between 1983–84 and 2013–16, and smaller between‐year changes in the contemporary dataset. Nine indicator species of the historic dataset were identified. Most were mayflies, particularly Baetidae, which were greatly reduced in relative abundance in 2013–16. Diptera became more numerous, and tanypodine chironomids were the sole contemporary indicator taxon. Relative abundance of eight of 19 drifting species (comprising 60% of total insects) was lower in 2013–16, when the dominant baetid mayfly during 1983–84 had declined by almost 90%; only one of the 19 species occurred at higher abundance. Eight species were affected by seasonal temperature variability, but these responses were not correlated with any tendency to exhibit long‐term changes in abundance. Substantial shifts in composition, including declines in mayfly relative abundance and assemblage diversity, occurred after three decades of warming, despite the broad annual range of stream temperatures (~16°C) in Hong Kong. This contradicts the well‐known prediction that organisms from variable climates have evolved wider thermal tolerances that reflect prevailing environmental conditions. The observed compositional reorganization indicates that variability, rather than stability, may be typical of undisturbed tropical stream communities. Abstract : One year of data on insect drift in a Hong Kong forest stream was compared with samples collected using the same methods over replicate years three decades later, when air temperatures had warmed by 0.5°C. Species richness had not changed, but true diversity was reduced. There were substantial shifts in assemblage composition: mayflies (especially Baetidae) had declined, while Diptera increased; the mayfly Liebebiella vera, which was the dominant species in 1983–84, declined by almost 90%. Variability, rather than stability, may be typical of tropical stream communities that have experienced moderate warming but are otherwise undisturbed.